Late diagnosis and vulnerabilities of the elderly living with HIV/AIDS - Alencar, Rubia Aguiar [UNESP]; Ciosak, Suely Itsuko (Univ Sao Paolo, 2015)
Objective: To identify vulnerabilities of elderly people with HIV/AIDS and the trajectory that they follow until reaching the diagnosis of the disease. Method: Qualitative research conducted in specialized clinics in the state of Sao Paulo, from January to June 2011. Semi-structured interviews were conducted with 11 elderly people who were found to be infected with the virus at the age of 60 years or older. The interviews were analyzed using content analysis. Results: In this process four categories emerged, then analyzed with reference to the theoretical framework of vulnerability. Conclusion: Late diagnosis of HIV infection or AIDS among the elderly happens in the secondary or tertiary service. Issues related to sexual life of the elderly are only questioned by health professionals after the diagnosis, also the time that condom use becomes absolute. It is believed that the investigation of the vulnerability of the elderly to HIV/AIDS allows for carrying out appropriate interventions for this population.

OBJETIVO: Identificar las vulnerabilidades de los ancianos con VIH/SIDA y el camino recorrido por ellos hasta el diagnóstico de la enfermedad. MÉTODO: Investigación cualitativa conducida en ambulatorio especializado en el interior del Estado de São Paulo, de enero a junio de 2011. Se llevó a cabo entrevista semiestructurada con 11 añosos que se descubrieron infectados con el virus en edad igual o superior a 60 años. Las entrevistas fueron valoradas utilizándose el análisis de contenido. RESULTADOS: De ese proceso surgieron cuatro categorías, las que se analizaron a la luz del marco de referencia teórico de la vulnerabilidad. CONCLUSIÓN: El diagnóstico tardío de la infección por VIH o SIDA entre los ancianos ocurre en el servicio secundario o terciario. Cuestiones relacionadas con la vida sexual de los ancianos sólo las cuestionan los profesionales de salud luego del diagnóstico de la enfermedad, momento también en que el uso del preservativo se hace concreto. Se cree que la investigación de la vulnerabilidad del anciano al VIH/SIDA posibilita realizar intervenciones pertinentes a dicha población.
El diagnóstico tardío y las vulnerabilidades de los ancianos que tienen vih/sida
Keywords: Elderly; Vulnerability; Acquired Immunodeficiency Syndrome; HIV; Delayed Diagnosis; Public Health Nursing; Anciano; Vulnerabilidad; Síndrome de Inmunodeficiencia Adquirida; VIH; Diagnóstico Tardío; Enfermería en Salud Pública